Smoking habits, knowledge and smoking attitudes among primary healthcare workers in Perak, Malaysia - Low Pei Kit; Hazizi Abu Saad; Rosita Jamaluddin; Chee Huei Phing (International Journal of Public Health Science (IJPHS), 2023)
A cross-sectional study was carried out to assess the smoking habits of primary healthcare workers, their knowledge about the harmful effects and health risks of smoking, as well as their attitudes towards not smoking. A validated self-administered questionnaire was used to collect the data. There were 261 primary healthcare workers in Perak, Malaysia recruited in this study. The results showed that there were only 4.6% (n=12) ever smokers and 2.7% (n=7) current smokers in this study. More than 75% of primary healthcare workers reported having friends and family members who smoked. The majority of the primary healthcare workers had good knowledge regarding the health risks and harmful effects of smoking. They also possessed positive attitudes towards not smoking. The females, those in the high-income group, the health service providers and the non-smokers had significantly higher scores in both their knowledge about smoking and positive attitudes towards not smoking (p<0.05). The primary healthcare workers with tertiary educational levels were significantly associated with positive attitudes towards not smoking (p<0.05). Gender and occupational status were the strongest predictors for knowledge about the health risks of smoking (p≤0.001), knowledge about the harmful effects of smoking (p≤0.001) and attitudes towards not smoking (p≤0.001). Health service providers, and females had the highest awareness of smoking. The high percentage of health service providers reported having friends and family members who smoked in this study should be given more attention. Implementation of more free-smoke areas could be use as strategy to reduce exposure to second-hand tobacco smoke.